The Relationship Between Parenting Styles and Violent Behavior in Adolescent Inmates - Setyowati, Wahyu Endang; Khalwati, Ulya Rakhmah; Febriana, Betie; Chan, Chong Mei (Adi Husada Nursing Journal, 2025)
Adolescence is a critical developmental period marked by identity exploration and vulnerability to negative influences, with parenting playing a significant role in shaping behavior. This study investigates the relationship between parenting styles and violent behavior among adolescent inmates, focusing on two correctional institutions. The research employed a cross-sectional quantitative design, utilizing questionnaires to collect data from adolescent inmates in two prisons. The analysis focused on identifying the predominant parenting styles experienced by the inmates and the prevalence of violent behavior within this population. The findings revealed that authoritarian parenting was the most common style reported by respondents, and a high level of violent behavior was observed among the inmates. Statistical analysis (p-value=0.001) demonstrated a strong and significant correlation between authoritarian parenting and the occurrence of violent behavior, indicating that strict and inflexible parenting approaches contribute to the development of aggression in adolescents. These results underscore the importance of fostering positive parenting practices and providing targeted interventions in correctional settings to reduce violence among adolescents. Low educational attainment and external factors, such as peer influence and family instability, further exacerbate violent tendencies. Understanding the impact of parenting styles is essential for developing effective prevention and rehabilitation strategies for young offenders.